Penerapan Sistem Pelaporan Bullying Berbasis Administrasi Kesehatan Sekolah yang Ramah Anak - Nur Akifa Sartika Putri; Aulia Apriliani; Suci Safwa Salsabila (Jurnal Pengabdian Bidang Kesehatan, 2026)
Bullying in the school environment is a social health problem that has a massive impact on children’s physical, mental, and social well-being. As the primary educational environment, schools need to implement a structured, safe, and child-friendly bullying reporting system. Objective: This conceptual study aims to design the implementation of a bullying reporting system based on school health administration using the functional management approach: planning, organizing, actuating, and controlling (POAC). The methods and components of the reporting system are designed through the four POAC pillars, namely the establishment of an Anti-Bullying Team, the preparation of Standard Operating Procedures (SOPs), the provision of child-friendly reporting media both physical and digital through the School Health Unit (UKS), and the development of monitoring and evaluation mechanisms (controlling). School health administration is used as an initial screening tool to identify indications of victim trauma discreetly and safely. The implementation of this POAC-based system is expected to improve the early detection of bullying cases, accelerate case handling responses, and eliminate stigma and fear of reporting among children. Conclusion: The integration of health administration and POAC management has proven to be a strong framework for creating a safe, inclusive school environment that strongly supports students’ mental health recovery.